1楼:匿名用户
写成-3/4×1又1/3÷(-1又1/2)÷1/5 =-(3/4)×(4/3)÷(-3/2)÷(1/5) =-1x(-2/3)x5 =2/3x5 =10/3好一些
(-3/5)x(-3又1/2)÷(-1又1/4)÷3
2楼:匿名用户
(-3/5)x(-3又1/2)÷(-1又1/4)÷3=(-3/5)x(-7/2)÷(-5/4)÷3= - 3/5 x 7/2 x 4/5 x 1/3= - 14/25
(-49)÷(-2又1/3)÷7/3除以(-3)=(-49)÷(-7/3)÷ 7/3 ÷ (-3)= - 49 × 3/7 × 3/7 ×1/3= - 3
3楼:新野旁观者
(-3/5)x(-3又1/2)÷(-1又1/4)÷3=-(3/5×
1/3)×(7/2×5/4)
=-1/5×35/8
=-7/8
(-49)÷(-2又1/3)÷7/3除以(-3)=-49×3/7×3/7×1/3
=-21×3/7×1/3
=-9×1/3=-3
4楼:徐秀平不是我
(-3/5)x(-3又1/2)÷(-1又1/4)÷3=(-3/5)x(-7/2)÷(-5/4)÷3= - 3/5 x 7/2 x 4/5 x 1/3= - 14/25
(-3/5)×(-3又1/2)÷(-1又1/4)÷3计算,要过程
5楼:匿名用户
-3/5(-7/2)(-4/5)1/3=-14/25
四又1/3-3又1/2×(-2)-2又2/3÷(-1/2)
6楼:匿名用户
=(4+1/3)-(3+1/2)×(-2)-(2+2/3)×(-2)=4+1/3+6+1+4+4/3
=15+5/3
=16又3分之2
4(3 3)X36 ,3/7X1/4÷3/4 (3/8+2/3)X36 7/5X2/3+14/15÷1/9 13/12÷(3/4+1/3) 给答案,我看对不对,如果有过程的
1楼 匿名用户 3 7x1 4 3 4 3 7x1 4x4 3 1 7 3 8 2 3 x36 3 8x36 2 3x36 37 5 7 5x2 3 14 15 1 9 14 15 14 15x9 14 15 1 9 9又1 3 13 12 3 4 1 3 13 12x12 13 1 简算 3 4 ...